Case report: Development of central precocious puberty in a girl with late-diagnosed simple virilizing congenital adrenal hyperplasia complicated with Williams syndrome - Joo, Eun Young; Yoo, Myung Ji; Kim, Su Jin; Jang, Woori; Lee, Ji-Eun (Frontiers in Endocrinology, 2024)
Congenital adrenal hyperplasia (CAH) and Williams Syndrome (WS; MIM # 194050) are distinct genetic conditions characterized by unique clinical features. 21-Hydroxylase deficiency (21-OHD; MIM #201910), the most common form of CAH, arises from mutations in the CYP21A2 gene, resulting in virilization of the external genitalia in affected females, early puberty in males, and short stature. Williams syndrome, caused by a microdeletion of 7q11.23, presents with distinctive facial features, intellectual disability, unique personality traits, early puberty, and short stature. This case report describe the clinical features of a 4-year-old girl referred due to progressive virilization and developmental delay. Genetic analysis confirmed concurrent CAH and WS, identifying a novel mutation in the CYP21A2 gene (c.1442T>C). Following corticosteroid therapy initiation, the patient developed central precocious puberty. This case report delves into the pubertal change patterns in a patient affected by overlapping genetic conditions, providing valuable insights in to the intricate clinical manifestation and management of these rare complex disorders.